Comparison of inorganic electron transport layers in fully roll-to-roll coated/printed organic photovoltaics in normal geometry. Issue 41 (26th September 2016) - Andersen, Thomas R.; Almyahi, Furqan; Cooling, Nathan A.; Elkington, Daniel; Wiggins, Lauren; Fahy, Adam; Feron, Krishna; Vaughan, Ben; Griffith, Matthew J.; Mozer, Attila J.; Sae-kung, Chaiyuth; Wallace, Gordon G.; et al.
Abstract : Four different inorganic materials as electrode transport layers in fully roll-to-roll P3HT:ICxA organic solar cells were investigated. Abstract : We investigate the suitability of four different inorganic materials (chromium oxide (CrO X ), titanium oxide (TiO X ), aluminium doped zinc oxide (AZO) and zinc oxide (ZnO)) as electrode transport layers in fully roll-to-roll (R2R) fabricated P3HT:ICxA organic solar cells. CrO X and TiO X were found to be unsuitable, as the CrO X devices did not exhibit rectifying behaviour while the TiO X devices did not withstand the annealing conditions. Of the last two ETLs, ZnO showed by far the most promise with devices demonstrating an average efficiency of 2.2%, which is the highest reported value for R2R devices in normal geometry, and a significantly extended lifetime compared with AZO devices under ISOS-L-2 conditions.